Frailty: an emerging geriatric syndrome - Ángel Julio Romero Carbrera (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2010)
In the last decade frailty has been increasingly regarded as an independent geriatric syndrome characterized by diminished physiological stores and rising health-risk vulnerability in elderlies. The present actualization provides a wide review on the topic by emphasizing aspects such as its definition, prevalence, etiopathogenia, conditioners or markers, clinical presentation, measurement tools, consequences and actions for its prevention and treatment.